The Philosophical Worth of Liberal Peacebuilding - Kharisma, Muhammad Waffa (Global: Jurnal Politik Internasional, 2017)
The concept of Liberal Peacebuilding is often associated with the failure of pushing liberalisation in war-torn failed states: the practice of liberal peacebuilding as a liberal project instead of a peacebuilding effort. The essay starts with breaking down the basic premises of a liberal peacebuilding and its ideological drive. Then, it identifies and evaluates the critics and alternatives to liberal peacebuilding. The essay sees that the implementation of fixed standard peacebuilding packages in vastly different scenarios and countries is the consequence of practicing liberal peacebuilding as a liberal project. This essay argues that liberal peacebuilding is worth saving if it recognises itself as an unfinished project, and instead advocates peacebuilding efforts that are more concentrated as a (and in showing) technical solution rather than an ideological impulse. As such, the essay proposes the prioritisation of maintaining stability in a post-conflict state, through concentrating on ensuring the specific case-per-case technical solutions, often which is attributed to institutional foundation to ensure the deliveries of collective aims and interests of local society.